A Dendrite‐Free Lithium‐Metal Anode Enabled by Designed Ultrathin MgF2 Nanosheets Encapsulated Inside Nitrogen‐Doped Graphene‐Like Hollow Nanospheres (Adv. Mater. 24/2022). Issue 24 (16th June 2022) - Li, Shang‐Qi; Zhang, Ling; Liu, Ting‐Ting; Zhang, Yao‐Wen; Guo, Chaofei; Wang, Yong; Du, Fei‐Hu
Abstract : Lithium‐Metal Anodes In article number 2201801, Yong Wang, Fei‐Hu Du, and co‐workers elaborately design ultrathin MgF2 nanosheets encapsulated inside N‐doped graphene‐like hollow nanospheres for a dendrite‐free lithium‐metal anode. A comprehensive and systematic study of the deposition behavior and mechanism of this hybrid host is presented. When assembled with LiFePO4 as a full cell, it exhibits excellent electrochemical properties.